Physical activity, cardiorespiratory fitness and the incidence of type 2 diabetes in a prospective study of men. Issue 4 (26th July 2009) - Sieverdes, John C; Sui, Xuemei; Lee, Duck-chul; Church, Timothy S; McClain, Amanda; Hand, Gregory A; Blair, Steven N
Abstract : Objective: To assess the independent and joint associations between self-reported physical activity (PA) and objectively measured cardiorespiratory fitness (CRF) from a maximal treadmill exercise test and the development of type 2 diabetes mellitus in a large cohort of men. Methods: Participants for the current analysis were 23 444 men aged 20–85 years free of cardiovascular disease (CVD), cancer or diabetes at baseline. Incident diabetes were identified from mail-back surveys. Cox regression analysis was used to estimate hazard ratios (HRs), 95% confidence intervals (CIs) and diabetes incidence rates (per 10 000 man-years) according to exposure categories. Results: During an average of 18 years of follow-up, 589 incident cases of diabetes were identified. After adjusting for age, examination year, survey response pattern, body mass index, smoking, drinking, fasting glucose, chronic diseases and family history of CVD or diabetes, the walking/jogging/running (WJR) and sport/fitness groups had a 40% and 28% lower risk of developing diabetes compared with the sedentary men, respectively (both p < 0.05). For CRF, diabetes incidence rates were 31.9, 14.5 and 6.5 for low-, moderate- and high-fitness groups, respectively. After adjustment for the above covariables, moderate and high CRF had a 38% and 63% lower risk of developing diabetes compared with the low CRF group (p trend<0.0001). Conclusion: Our findings showed a lower risk of developing diabetes for men who participated in a WJR programme or sport/fitness activity, compared with those who were sedentary. Higher levels of fitness were associated with an inverse gradient of incident diabetes.